The Effect of Intellectual Intelligence, Learning Motivation, Learning Behavior on interest in learning Computer Accounting at Imelda University Medan students - Monang Juanda Tua Sihombing (SEAN Institute, 2023)
This study aims to analyze the effect of intellectual intelligence, learning motivation, learning behavior on interest in learning computer accounting in Imelda University students in Medan. Intellectual intelligence alone is not able to be relied upon in understanding lessons to start an activity will have a feeling of laziness and not interested in continuing their activities without being balanced with strong learning motivation and enthusiasm causing concentration and attention to lessons will decrease so that low learning behavior will reflect a lack of attitude. both from the student himself in responding and responding to every teaching and learning activity that occurs and is not responsible for the learning opportunities given to him. The analytical method used in this study is a quantitative method by testing the classical assumptions, as well as statistical analysis, namely multiple regression analysis. The total population in this study were 240 students. the sample used was 130 students using a sampling technique with the Cluster Random Sampling method. Students are required to study harder so giving rewards is necessary so that students are motivated to learn. Learning behavior in accordance with educational goals, where educational goals can be achieved effectively and efficiently, so that academic achievement can be improved